2012
DOI: 10.1021/om300695k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentadienyl-Based Amino Acids (Cp-aa) As Phenylalanine Analogues for Tumor Targeting: Syntheses and Biological Properties of [(Cp-aa)M(CO)3](M = Mn, Re, 99mTc)

Abstract: Due to an enhanced demand for amino acids, the l-type amino acid transporter 1 (LAT1) is overexpressed in many tumor cell lines. LAT1 represents therefore an attractive target for cancer therapy and diagnosis. On the basis of our reported aqueous synthesis of [(Cp-R)99mTc(CO)3]-type complexes, − we describe the preparation of unnatural amino acid analogues [(Cp-CH2CH(NH2)COOH)Mn(CO)3] and [(Cp-CH(NH2)COOH)M(CO)3] (M = Mn, Re, 99mTc). Starting from fully protected HC5H5-aa (aa = amino acid), [(Cp-aa)99mTc(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…9,12− 16 We previously reported studies on the preparation of [(Cp-R) 99m Tc(CO) 3 ] and its rhenium homologues. 10,11,17 The reaction of [ 99m Tc(OH 2 ) 3 (CO) 3 ] + (1) 18 with stable HCp-R monomers or Diels−Alder dimerized Cp derivatives (Thiele's acid [(C 5 H 5 -COOH) 2 ]) leads straight to [ ( C p -R ) 9 9 m T c ( C O ) 3 ] t y p e c o m p l e x e s i n h i g h yields. 10,11,17,19−21 Exploring the possibility of attaching more than one bioactive group, the soluble and water stable ligands Na[C 5 H 3 (1,2-COOMe) 2 ] (2) and Na[C 5 H 3 (1,3-COOMe) 2 ] (3) came to our attention.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9,12− 16 We previously reported studies on the preparation of [(Cp-R) 99m Tc(CO) 3 ] and its rhenium homologues. 10,11,17 The reaction of [ 99m Tc(OH 2 ) 3 (CO) 3 ] + (1) 18 with stable HCp-R monomers or Diels−Alder dimerized Cp derivatives (Thiele's acid [(C 5 H 5 -COOH) 2 ]) leads straight to [ ( C p -R ) 9 9 m T c ( C O ) 3 ] t y p e c o m p l e x e s i n h i g h yields. 10,11,17,19−21 Exploring the possibility of attaching more than one bioactive group, the soluble and water stable ligands Na[C 5 H 3 (1,2-COOMe) 2 ] (2) and Na[C 5 H 3 (1,3-COOMe) 2 ] (3) came to our attention.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similar yield of 6a (72%) was obtained with 1 equiv of AlCl 3 (entry 3). The reaction performed with other Lewis acids, Cu(OTf) 2 and Sc(OTf) 3 gave 6a in 70% and 73% yields, respectively, and slightly longer reaction times (entries [4][5], whereas with BF 3 .OEt 2 provided 79% yield within 15 min (entry 6). Reaction with protic acids such as triflic and methanesulfonic acids gave slightly lower yields 60% and 68%, respectively (entries 7-8).…”
Section: Resultsmentioning
confidence: 99%
“…While Alberto reported that the metal-mediated retro Diels-Alder reaction is a convenient method to prepare cytectrenes in aqueous solution [5,7], we demonstrated recently the use of microwave heating gave a novel impetus to the double-ligand transfer reaction [13]. Thus, using these conditions, i.e.…”
Section: Radiochemistrymentioning
confidence: 90%
“…Thus, [{R-Cp} 99m Tc(CO) 3 ] (R = organic part or biomolecule) were obtained in good yield by reacting the fac-[ 99m Tc(CO) 3 (H 2 O) 3 ] + core or directly the sodium pertechnetate, with Diels-Alder dimerized compounds like Thiele's acid [5,6]. Additionally, he exploited a similar procedure with monomeric Cp derivatives which yielded piano-stool complexes as well, after reaction with Tc(I) or Tc(VII) precursors in water [7]. The second and the oldest approach was first reported by Wenzel [8] and developed by Katzenellenbogen [9], Jaouen [10] and our group [11].…”
Section: Introductionmentioning
confidence: 99%